Adventures in crystal engineering - Tiekink, Edward R. T. * (Sunway University Press, 2018)
Crystals are all around us and are aesthetically pleasing as they arise from the ordered, three-dimensional assembly of chemical species which can be minerals (e.g. salt), macromolecules (e.g. proteins) or smaller chemical species (e.g. drugs, natural products, coordination complexes, etc.). Scientists need to know the precise structure of all these materials in order to rationalise the way they work. To put it in another way, “structure determines function”. Single-crystal X-ray crystallography is the crucial technique behind the determination of crystal structure. Despite the prevalence and obvious importance of crystals, what remains an enormous challenge in contemporary science is to answer the fundamental question of “How do crystals form?”. The goal of crystal engineering is to control the way molecules self-assemble in the condensed phase and the present discussion relates to this topic, an on-going research programme undertaken at Sunway University.